Distinctive effects of fear and sadness induction on anger and aggressive behavior - Zhan, Jun; Ren, Jun; Fan, Jin; Luo, Jing (Frontiers in Psychology, 2015)
A recent study has reported that the successful implementation of cognitive regulation of emotion depends on higher-level cognitive functions, such as top-down control, which may be impaired in stressful situations. This calls for a need of “cognition free” self-regulatory strategies that do not require top-down control. In contrast to the cognitive regulation of emotion that emphasizes the role of cognition, traditional Chinese philosophy and medicine views the relationship among different types of emotions as promoting or counteracting each other, without the involvement of cognition, which provides an insightful perspective for developing “cognition free” regulatory strategies. In this study, we examined two hypotheses regarding the modulation of anger and aggressive behavior: sadness counteracts anger or aggressive behavior, whereas fear promotes anger or aggressive behavior. Participants were first provoked by reading the extremely negative feedback on their viewpoints (Study 1) or by watching anger-inducing movie clips (Study 2); then, these angry participants were assigned to three equivalent groups and view sad, fear, or neutral materials respectively to evoke the corresponding emotions. The results found participants yielded a lower level of aggressive behavior when sadness was induced afterward, and a higher level of anger when fear was induced afterward. These results provided evidence supporting the hypothesis of mutual promotion or counteraction relationships among these types of emotion and implied a “cognition free” approach for regulating anger and aggressive behavior.